USM SCHOOL RECEIVES CABE UK VISIT, 2 COURSES RECOGNISED - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 11 October 2016 Universiti Sains Malaysia (USM) recently received a visit from the President and Chief Executive Officer (CEO) of Chartered Association of Building Engineer (CABE) United Kingdom, Ben Bradford and Dr. John Hooper.